Switch rates do not influence weighting of rare events in decisions from experience, but optional stopping does. (6th April 2018) - Soo, Kevin W.; Rottman, Benjamin M.
Abstract: The current research investigates how people decide which of two options produces a better reward by repeatedly sampling from the options. In particular, it investigates the roles of two features of search, optional stopping and switch rate, on participants' final judgments of which option is better. First, in two studies, we found evidence for a new optional stopping effect; when participants stopped sampling right after experiencing a rare outcome, they made decisions as if they overweighted the rare outcome. Second, we investigated an effect proposed by Hills and Hertwig (2010) that people who frequently switch between options when sampling are more likely to make decisions consistent with underweighting rare outcomes. We conducted a theoretical analysis examining how switch rate can influence underweighting and how the type of decision problem moderates this effect. Informed by the theoretical analysis, we conducted four studies designed to test this effect with high power. None of the studies produced significant effects of switch rate. Lastly, the studies replicated a prior finding that optional stopping and switch rate are negatively correlated. In sum, this research elaborates a fuller understanding of the relation between search strategies (switch rate and optional stopping) on how people decide which option is better and their tendency to overweight versus underweight rare outcomes.